Logo modernism - Müller, Jens 1982-; Wiedemann, Julius; Remington, R. Roger; Varea Riley, Isabel; Wulfekamp, Ursula; Fruhtrunk, Wolf (Köln : Taschen, 2018)
"Examine Modernism's distillation in graphic design with this vast collection of approximately 6,000 logos from 1940-1980. Ranging from media outfits to retail giant, airlines to art galleries, these clean, clear logo concepts may be seen as the visual birth of corporate identity"--Jacket.
Logo / Jens Müller -- Viva modernism! / R. Roger Remington -- Geometric. Angular ; Arrow ; Basic forms ; Circle ; Case study : Daiei ; Cross ; Dots ; Figurative ; Lines ; Case study: Mexico '68 ; Skewed ; Case study: Fiat ; Round ; Square ; Triangle -- Effect. Cut-off ; Case study : Claude Neon ; Split ; Duplication ; Grid ; Reflection ; Outline ; Overlay ; Positive/negative ; Case study : De Ploeg ; Rotation ; Three-dimensional ; White on black -- Typographic. A to Z ; Case study : Atlas Film ; Opened-up letters ; Case study : London Electricity Board ; Two letters ; Three letters ; Case study : Deutscher Taschenbuch Verlag ; Words -- Profiles. Adrian Frutiger ; Paul Ibou ; Yusaku Kamekura ; Stefan Kanchev ; Burton Kramer ; Paul Rand ; Karol Sliwka ; Anton Stankowski.
Includes bibliographical references (pages 427-429) and index.
CSE
Karim International
Text in English, French, and German.
Keywords: Logotypes (Printing) -- Pictorial works; Logos (Symbols) -- Pictorial works; Trademarks -- Pictorial works; Logotypes (Printing); Logos (Symbols); Commercial art; Advertising; Advertising; Commercial art; Logos (Symbols); Logotypes (Printing); Trademarks; Computer science; Pictorial works